Model of Arabic Curriculum Development in Traditional Islamic Boarding Schools: A Case Study in Pesantren Musthafawiyah Purba Baru and Dayah Mudi Mesra Samalanga - Setiadi, Fadlan Masykura; Khairul Fuadi; Irmasani Daulay (STUDI ARAB, 2022)
This research aims to describe the Arabic language curriculum development model that is carried out at the Musthafawiyah Islamic Boarding School, North Sumatra, and Dayah Mudi Mesra, Samalanga, Aceh. This research uses a case study approach with data collection techniques in the form of observation, interviews, and documentation. The results of the research show that the Arabic language curriculum development model at the Musthafawiyah Islamic Boarding School Purba Baru and Dayah Mudi Mesra Samalanga has undergone stages of development in planning, organizing, implementing, and evaluating. First, the Arabic language curriculum development model at the Musthafawiyah Islamic Boarding School Purba Baru and Dayah Mudi Mesra Samalanga includes the following steps: a) formulating the vision, mission, and learning objectives to be achieved; b) maximizing the needs of students, graduate user communities, and further studies; c) curriculum evaluation; and d) adaptation to current needs. Second, the Arabic curriculum model used in the Old Musthafawiyah Islamic Boarding School and Dayah Mudi Mesra Samalanga is known as a separate curriculum model. In this curriculum model, listening skills, speaking skills, writing skills, reading skills, and grammar learning are taught separately.